MITRAL VALVE REPLACEMENT AT 11 YEARS OLD GIRL WITH RHEUMATIC MITRAL STENOSIS - Malik, Suryani; Gunawijaya, Eka; Yasa, Ketut Putu (Medicina, 2015)
Rheumatic heart disease (RHD) is the permanent heart valve damage resulting from one or more attacks of acute rheumatic fever (ARF), representing the permanent lesions of the cardiac valve. Rheumatic heart disease’s patient with valvar involvement usually require long term follow-up. The ultimate decision of clinical management or invasive therapy is made on an individual basis. We reported a 11-year-old girl with RHD and severe mitral stenosis whom underwent   mitral valve replacement with mechanical valve. Postoperative echocardiogram showed no mitral regurgitation and we gave anticoagulant to maintain INR of 3-4 by giving warfarin 2mg / kg each day for lifelong to prevent bleeding and thrombosis. [ MEDICINA 2014;45:120-6 ]
Keywords: rheumatic mitral stenosis, mitral valve replacement, children